2012
DOI: 10.1007/s00774-012-0349-1
|View full text |Cite
|
Sign up to set email alerts
|

Time to onset of efficacy in fracture reduction with current anti-osteoporosis treatments

Abstract: Early prevention of future fracture is an important goal in those at risk. A similar 3-year fracture efficacy is reported for most osteoporosis agents. Onset of fracture efficacy may be useful to help tailor treatment based on risk. We reviewed the peer-reviewed literature for onset of fracture efficacy data on the commonly prescribed osteoporosis treatments. All papers were reviewed independently by at least two reviewers for onset of efficacy for morphometric vertebral fracture (MVF), clinical vertebral frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 48 publications
1
31
0
1
Order By: Relevance
“…Compounding this issue is that the earliest demonstrated time to antiosteoporosis treatment efficacy in terms of hip fracture risk reduction is 6-36 months. 126 Specifically, zoledronic acid has been shown to reduce clinical fracture risk after hip fracture only after 12 months. 119 In the present analysis, 35% and 63% of second hip fractures within 2 years occurred within the first 6 and 12 months, respectively.…”
Section: Second Hip Fracturementioning
confidence: 99%
“…Compounding this issue is that the earliest demonstrated time to antiosteoporosis treatment efficacy in terms of hip fracture risk reduction is 6-36 months. 126 Specifically, zoledronic acid has been shown to reduce clinical fracture risk after hip fracture only after 12 months. 119 In the present analysis, 35% and 63% of second hip fractures within 2 years occurred within the first 6 and 12 months, respectively.…”
Section: Second Hip Fracturementioning
confidence: 99%
“…Our study has a shorter follow-up period compared to RCT and other RWE studies; therefore, the impact may be greater with a longer follow-up. Additionally, a systematic review of RCTs demonstrated the impact of osteoporosis medication on time to fracture reduction, ranging from 6-36 months of treatment [37]. Our RWE study results among Medicare women can be tied to the fact that osteoporosis treatments show an increased effectiveness against subsequent fractures and support the efficacy demonstrated through RCTs in the past.…”
Section: Discussionmentioning
confidence: 60%
“…Although few data are available in older groups [321], there is acceptable evidence to recommend the BPs, strontium ranelate, or teriparatide for vertebral fracture relative risk reduction (RRR) in persons aged > 75 years [311, 322]. A significant RRR of vertebral fracture at 1 year has been demonstrated for risedronate (RRR 81%; p<0.001), teriparatide (RRR 65%; p<0.05) and strontium ranelate (RRR 59%; p=0.002), and at 3 years for risedronate (RRR 44%; p=0.003), alendronate (RRR 38%; p<0.05), strontium ranelate (RR 32%; p=0.013) and denosumab in high risk fracture women (16.6% placebo vs. 7.5% denosumab; p< 0.001) [322].…”
Section: Intervention Strategies To Counteract Disability Associatmentioning
confidence: 99%
“…Concerning the non-vertebral fractures, there is evidence for protective effects of strontium ranelate after 1 and 3 years of treatment (RRR 41%; p=0.027 and RRR 31%; p=0.011) [311], for denosumab (HR 0.80; p=0.01) [321] and zoledronic acid (HR 0.73, p=0.002) after three years with efficacy almost superimposed to those of younger persons [325]. Risedronate demonstrated to reduce non-vertebral fracture only in a combined analysis of subjects participating in the HIP study (70–79 years and ≥80 years groups) [323].…”
Section: Intervention Strategies To Counteract Disability Associatmentioning
confidence: 99%
See 1 more Smart Citation